Marketing strategy of the Foriesta Sfera Sports 2.0 / Nurulasmida Mohd Zin and Muhammad Danial ‘Immran Mohd Fauzi - Mohd Zin, Nurulasmida; Mohd Fauzi, Muhammad Danial ‘Immran (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The Foriesta Sfera Sport 2.0 which was held on the 17th and 18th December 2022 took place at UiTM Seremban’s court and field. This particular sports event was monitored by one lecturer, Puan. Nur Dalilah Binti Dahlan and handled by a total of 65 semester three students of Bachelor’s Degree in Sports Management with cooperation from the faculty’s club which is also known as FoSRec. The first step in the planning phase is understanding consumers’ needs. The organizer included some information gathering during every meeting before the event to identify and specify what is the best activity and sports to be held on the incident day. This initiative was taken to fulfil the participants’ needs and to ensure that the program objectives could be met. The next step is the market selection decision. At first, they were about to organize a sports event that relates to traditional elements. However, after several verbal surveys done among students who live in in the campus’ college, they found that students would most likely not participate in the event if the organizer proceeds with the traditional theme because they prefer the program to be based on the original rules and regulations of each sport. This revelation prompted the organizers to cancel the first plan.